Germinated brown rice extract reduces brain lipid peroxidation and Aβ levels via regulations of BACE1, RAGE, IDE and LRP1 expressions in high fat/cholesterol diet-fed rats - Azmi, Nur Hanisah; Ismail, Norsharina; Imam, Mustapha Umar; Ooi, Der Jiun; Yida, Zhang; Abdul Aziz, Ahmad Hazim; Mohamad Rosdi, Mohamad Norisham (Elsevier, 2023)
A strong association presents between excessive amyloid-β (Aβ) buildup and oxidative stress with Alzheimer’s disease (AD). In view of the multifaceted neuroprotective effects of some dietary elements, the beneficial effect of germinated brown rice was investigated using a high fat/cholesterol diet (HFCD)-induced sporadic rat model of AD. Seven groups, including normal control, HFCD, and HFCD treated with Donepezil, Simvastatin, Probucol, and germinated brown rice ethyl acetate extract (GBR-EA; 100 and 200 mg/kg bw) were included in the present study. Biochemical assays, brain lipid peroxidation, mRNA and protein levels involved in Aβ processing and metabolism pathways were analyzed. HFCD-fed rats exhibited increased brain lipid peroxidation and Aβ levels, as well as altered expressions of proteins involved in Aβ generation, degradation and clearance. GBR-EA treatment groups showed significant reduction in lipid peroxidation and Aβ levels when compared to HFCD group. The effects of GBR-EA on Aβ levels are likely through the modulation of BACE1 and Presenilins, as well as induction of Aβ clearance and degradation. The findings revealed the potential use of germinated brown rice to attenuate HFCD diet-induced neurodegenerative alterations, likely due to reduced brain inflammation, as well as modulation of Aβ processing and metabolism pathways.